I still got it!

Anyone recognise the formula?

I just spent 20 minutes converting the formula…

d = M-((M/2)+7)

…into…

M = 2(d+7)

I still got it baby!

(Even if it would have taken me about a 10th of the time back in high school :))

The steps are…

d = M-((M/2)+7)
M = d+((M/2)+7)
M = d+7+(M*0.5)
M-(M*0.5) = d+7
(This one took me ages)
0.5*M = d+7
M = 2(d+7)

Now, does anyone recognise the base formula?

9 thoughts on “I still got it!”

  1. Why must you speak in tongues??? I do not understand your strange “language”

    Although, congrats for still “getting” it.

  2. Oh, and I forgot…

    m = d+14

    …which I think completes the full set of necessary formulae. Now if you have M, m or d you can easily derive the other two. Awesome!

Leave a Reply

Your email address will not be published. Required fields are marked *